Exile dreams: antifascist Jews, antisemitism and the ‘other Germany’ - Koch, Anna (Fascism, 2020)
This article examines the meanings antifascist German Jews invested in antifascism and highlights its role as an emotional place of belonging. The sense of belonging to a larger collective enabled antifascist Jews to hold onto their Germanness and believe in the possibility of an ‘other Germany’. While most German Jewish antifascists remained deeply invested in their home country in the 1930s, this idea of the ‘other Germany’ became increasingly difficult to uphold in the face of war and genocide. For some this belief received the final blow after the end of the Second World War when they returned and witnessed the construction of German states that fell short of the hopes they had nourished while in exile. Yet even though they became disillusioned with the ‘other Germany’, they remained attached to antifascism.